Binucleated Neuron as a Potential Histologic Marker of Neuroregeneration in Rat Sciatic Nerve Injury Model - Pryambodho Pryambodho; Ismail Hadisoebroto Dilogo; Aida Rosita Tantri; Renindra Ananda Aman; Tjokorda Gde Agung Senapathi; Yetty Ramli; Nuryati Chairani Siregar; Indah Suci Widyahening; Fitriya Nur Annisa Dewi (Bali Journal of Anesthesiology)
Background: The rat sciatic nerve injury model is one of the most studied models for peripheral nerve injury. Mesenchymal stem cells (MSCs) are known to induce neuroregeneration in this rat model. The most common methods to quantify neuroregeneration in peripheral nerves include histomorphometric analysis of axonal count, length, and mean axonal area. However, histomorphometric analysis remains vague for dorsal root ganglion (DRG). It is known that binucleated neurons (BNs) are present in normal rat populations, increase following the transplantation of bone marrow-derived cells into the cerebellum, and disappear with inflammation. We propose a new potential histologic marker as a probable alternative to conventional axonal histomorphometric analysis for DRG in the Sprague Dawley rat sciatic nerve injury model. Materials and Methods: A total of 32 Sprague Dawley rats were involved in this study, 30 rats were subjected to sciatic chronic constriction injury (CCI) to develop a neuropathic pain model. The rats were randomized into two groups, which received intrathecal normal saline injection (NSI) or stem cell injection (SCI). Human MSCs were intrathecally delivered using ultrasound-guided injection, 7 days after ligation (D7). Samples of DRG were obtained from normal rats (n = 2), from both groups on day 0 (D0), day 14 (D14), and day 28 (D28) post-CCI, analyzing DRG structures of BN. Results: CCI causes neuropathic pain, confirmed using Von Frey at D7, D14, and D28. Histologically, neuroregeneration was observed starting from D14 and D28. Histomorphological analysis revealed BN present exclusively in the SCI group compared with the NSI group. Conclusion: BN may serve as a potential marker for early neuroregeneration in rat sciatic nerve injury models.